Steering through the landscape: a study on entrepreneurs' perceptions of business environments - Gelmar García-Vidal; Laritza Guzmán-Vilar; Alexander Sánchez-Rodríguez; Reyner Pérez-Campdesuñer; Rodobaldo Martínez-Vivar (Serbian Journal of Management)
The purpose of this research is to analyze the perception of the environment by SME owners and managers. The research methodology used in this study involved collecting information from 384 SME owners-managers from different sectors of the economy in Santo Domingo de los Tsáchilas, Ecuador. Proportional stratified sampling was used with 95% confidence and an error of 5%. The data was collected through a self-administered cross-sectional survey questionnaire that aimed to get SME owner-managers to describe how they perceive their environment making a combination of the value of each variable. The study applied categorical principal component analysis (CATPCA) to identify the component structure of social capital by considering the ordinal and nominal nature of the data. The methodology used allowed us to understand the perception of the environment by different SME owner-managers from different sectors of the economy. It also revealed the strategic approach they considered most appropriate to the market situation in which they operate. The practical implications of this research suggest that SME owner-managers can benefit from understanding the perception of the environment by adopting flexible and adaptable solutions to changing environmental conditions, using environmental profiles to uncover opportunities, and anticipating changes to gain valuable insights.